Diagnostic Workup and Treatment of a Rare Apocrine Hidrocystoma Affecting the Oral Mucosa: A Clinical and Histological Case Report. (11th July 2017) - Poli, Pier Paolo; Creminelli, Luca; Moramarco, Valeria; Del Gobbo, Alessandro; Ferrante, Franco; Maiorana, Carlo
Abstract : Apocrine hidrocystomas are rare benign cystic tumors originating from the secretory portion of apocrine sweat glands. To the best of our knowledge, there is no evidence currently available reporting the presence of apocrine hidrocystomas in the oral cavity. Therefore, this case report aims to describe the clinical and histological features of an apocrine hidrocystoma affecting the oral mucosa. A 69-year-old male patient presented with a 1-year history of a solitary, well-circumscribed, submucosal mass in the left posterior buccal mucosa. The clinical examination revealed a yellowish soft, fluctuant, and painless lesion with no clinical signs of erythema or ulcerations of the overlying epithelium. The entire lesion was excised and histopathological analysis confirmed the diagnosis of apocrine hidrocystoma. No recurrence was observed after a 1-year follow-up.